Gendered Ageism in Australia: Changing Perceptions of Age Discrimination among Older Men and Women1. Issue 4 (26th September 2016) - McGann, Michael; Ong, Rachel; Bowman, Dina; Duncan, Alan; Kimberley, Helen; Biggs, Simon
Abstract : This paper investigates how age and gender interact to shape older jobseekers' experiences of age discrimination within a mixed methods framework. The analysis reveals that there has been a considerable decline in national levels of perceived ageism generally among older men relative to older women. These research findings suggest that the nature of ageism experienced by older women is qualitatively different from men. Currently, one‐size‐fits‐all, business case approaches rely on an overly narrow concept that obscures the gender and occupational dimensions of ageism. Hence, policy responses to ageism need to be far more tailored in their approach.